Adoption and Usage Patterns of Smart Television among Different Demographics of University Staff in Nigeria. - Talabi, Felix Olajide; Amos Daniel, Henry; Oladele, Patrick Olajide; Ogah, Abari Ijuo; Okunade, Joshua Kayode; Aiyesimoju, Ayodeji Boluwatife; Bello, Samson Adedapo; Zannu, Prosper Nunayon; Aderibigbe, Adebola Adewunmi; Ogundeji, Benjamin Kayode (Journal of African Film & Diaspora Studies (JAFDIS), 2024)
The ability of smart televisions to connect to the Internet, stream content online, and host its applications and software makes it an exciting innovation in broadcasting. Understanding the factors influencing the adoption of smart televisions is crucial due to their increasing popularity over time. The study aims to identify factors that influence the adoption of smart televisions and examines its effect on the consumption of traditional broadcast media among different demographics of university staff. The study used a mixed-method approach and stratified sampling to elicit information from 262 respondents, and demographic variables were analysed using frequency percentages in tables. Quantitative data showed that the major factor for smart TVs' adoption is their advanced features (M=3.85; SD=.94); also, for the major factor on Smart TVs usage, they identified that smart TVs have replaced traditional TVs (M=4.14; SD: = 0.14). The findings from qualitative data revealed that the convenience of accessing streaming services, Internet connectivity, and integration of social applications were the driving factors in the adoption and usage of smart television. Data also showed that streaming services influence the usage patterns of smart television, such as Netflix, playing games, consuming news channels, streaming, and listening to music. Furthermore, it was deduced that smart television has the potential to replace traditional TV due to consumers' interest in its features, such as streaming services. The study concluded that smart televisions are emerging as Nigeria's primary hub for home entertainment in all spheres of life. Thus, the implication is that different demographic respondents have embraced smart TVs in Nigeria due to the influencing factors.